What Doesn't Kill You Will Only Make You More Risk‐Loving: Early‐Life Disasters and CEO Behavior - BERNILE, GENNARO; BHAGWAT, VINEET; RAU, P. RAGHAVENDRA (Journal of Finance, 2017)
ABSTRACT The literature on managerial style posits a linear relation between a chief executive officer's (CEOs) past experiences and firm risk. We show that there is a nonmonotonic relation between the intensity of CEOs’ early‐life exposure to fatal disasters and corporate risk‐taking. CEOs who experience fatal disasters without extremely negative consequences lead firms that behave more aggressively, whereas CEOs who witness the extreme downside of disasters behave more conservatively. These patterns manifest across various corporate policies including leverage, cash holdings, and acquisition activity. Ultimately, the link between CEOs’ disaster experience and corporate policies has real economic consequences on firm riskiness and cost of capital.